Long-term observation of the patient after CABG with asymptomatic high-grade aortic regurgitation – a clinical case study - Szydełko, Joanna; Szydełko, Magdalena; Tuzim, Kamila; Piątek, Daniel; Mazur-Stążka, Elżbieta; Trojnar, Michał (Journal of Education, Health and Sport, 2019)
Introduction: The aortic valve regurgitation (AR) is a heart defect consisting of the retrograde flow of blood from the aorta to the left ventricle due to the improper closure of the aortic valve leaflets. It occurs approximately in 13% of men and 8.5% of women, and the incidence increases with age. A crucial issue in regards to a patient with asymptomatic AR, especially of a high degree, is determination of the time of qualification for invasive treatment.Aim: To draw attention to the necessity of holistic approach to a patient with asymptomatic high-grade aortic regurgitation. Moreover, the complications of delayed implementation of invasive treatment were discussed.Case report: A clinical case of a 62-year-old patient with a history of coronary artery bypass grafting and with AR – stage II, accidentally detected two years later in a control echocardiogram, was presented. Despite gradual progress of regurgitation, none of the disturbing symptoms were noted, whereas cardiac parameters were systematically monitored using ECG, ECHO and CT imaging. Beta blockers, ACE inhibitors, loop diuretics and aspirin were used as conservative treatment. After 10-year transthoracic echocardiographic follow-up due to progression of AR and development of heart failure, the patient was qualified to surgical replacement of the aortic valve. This procedure significantly improved the patient's quality of life.Summary: The key element in the treatment of chronic asymptomatic AR is the individualization of the therapy. An essential role is played by appropriate pharmacotherapy, precise monitoring using transthoracic echocardiography, which is recommended as the first-line imaging strategy. Delaying in the implementation of surgical treatment may result in failure of the therapy and the onset of serious complications.